Antitumor property of snakes’ venom of the genus Coluber - U., Iriskulov B.; E.A., Rakhmatullaev (International Journal of Psychosocial Rehabilitation, 2020)
This article presents data on histological, electron microscopic, and biochemical methods for studying the venom of snakes of the genus Coluber. The effect of Coluber snake venom on antitumor activity was studied. We studied the parameters of T-helper activity and indicators of the chemokine RANTES. The results of the study suggest that the poisons of the Coluber genus have antitumor properties, which is confirmed by the results of the studies.